2012
DOI: 10.4102/curationis.v35i1.87
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life domains relevant to people living with HIV and AIDS who are on antiretroviral therapy in Swaziland

Abstract: Quality of life (QOL) domains that are context specific to people living with HIV and AIDS (PLWHA) who are on antiretroviral therapy (ART) in Swaziland are unknown. This presents a problem when research has to be conducted on QOL of PLWHA who are on ART. As a result, this study was conducted to identify, validate and describe domains necessary to assess QOL of PLWHA, who are on ART in Swaziland. A qualitative, explorative, descriptive, and contextual design was used for this study. The first phase dealt with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Consequently, to increase the length and quality of survival of PLWHA who are on ART, it is essential that an evaluation of their QoL becomes more important than quantity of life. ART may indeed prolong life but may only do so at considerable cost to the QoL of PLWHA [17]. There is a geographical discrepancy in HIV/AIDS economic evaluation research [18].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to increase the length and quality of survival of PLWHA who are on ART, it is essential that an evaluation of their QoL becomes more important than quantity of life. ART may indeed prolong life but may only do so at considerable cost to the QoL of PLWHA [17]. There is a geographical discrepancy in HIV/AIDS economic evaluation research [18].…”
Section: Introductionmentioning
confidence: 99%
“…ART defaulters in this study might have discontinued their ART when they became more focused on spirituality and religion as coping mechanisms, but this could not be confirmed nor denied based on the available information. Ntshakala 17 studied the QoL of ART patients in Swaziland and found that spirituality conflicted with ART adherence. Other researchers reported similar associations between spirituality and HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that PLWHA who experienced challenges in coping with ART had poorer ART adherence levels and poorer HRQoL mean scores compared to PLWHA without such challenges. 17 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…HAART may lengthen life, but at a significant cost to the HRQoL of HIV-infected people. 13 The more HAART improves the QoL of patients, the more difficult it becomes to maintain frequent contact with healthcare providers, leading to monthly appointments to obtain HAART being missed. 14 On the other hand, the assessment of HRQoL in these patients has become important, as their well-being may be affected not only by treatment failure but also by other treatmentrelated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the QoL of people taking HAART has also been measured by the presence or absence of side effects of HAART. 13 In Ethiopia, HIV/AIDS has been recognized not only as a health problem, but also as a development challenge. Despite the efforts to contain the spread of the infection and prolong the lives of infected people by increasing access to antiretroviral drugs and improving clinical care, there has been less focus on patients' QoL and associated factors in the country.…”
Section: Introductionmentioning
confidence: 99%